KAJIAN PRINSIP PSIKOLOGI ARSITEKTUR PADA PANDUAN SEKOLAH RAMAH ANAK - Sarasati, Carina (JURNAL PERSPEKTIF ARSITEKTUR, 2024)
Education plays a vital role in children's lives, both now and in the future. To support this, the United Nations, through UNICEF, has developed guidelines for Child-Friendly Schools (CFS) since 2009. These guidelines aim to create safe and comfortable learning environments that meet all children's educational needs. The design of schools also plays a significant role in shaping the learning environment by creating spaces that cater to children's developmental needs and behaviors. However, the current CFS guidelines do not explicitly mention the use of architectural psychology studies. Instead, they focus more on creating a child-friendly learning environment. Therefore, the purpose of this research is to examine how architectural psychology principles can be applied to the Child-Friendly School Guidelines. This will be achieved through a literature review comparing architectural psychology theories that can be applied to the design of Child-Friendly Schools. The study's results indicate that the existing CFS guidelines have considered the principles of architectural psychology. However, for detailed technical implementation, further references are needed, especially regarding accessibility and safety, architectural form, proportion and scale, and furniture design.